Integrating bioinformatics in the teaching and redesign of the course Applied Microbiology - C. Hennessy, Roseanna (Improving University Science Teaching and Learning, 2023)
The emergence and rapid development of high-throughput DNA sequensing technologies has greatly impacted the biological sciences making many disciplines including microbiology more computationally intensive (Cummings & Temple, 2010; Macori et al., 2017). As a result, there is an increasing demand for researchers with skills in both lab-based techniques and bioinformatics (Mikheyev & Arora, 2015). Consequently, the successful incorporation of bioinformatics into wet-lab study lines is critical. The Master level course Applied Microbiology is a popular course that receives good evaluations year to year. However, the bioinformatics-based theme “microbial genomics” recurrently poses a challenge to students. The objective of this paper is to provide an in-depth analysis of the current course with a focus on how to integrate bioinformatics. The reflection and analysis provided here will serve as a white paper for the revision and long-term redesign of the course.